The Study of Hemodialysis on the Change Rate of Serum Osteopontin, Sialic Acid, and Nitric Oxide Levels - Entedhar R. Sarhat; Takea Shaker Ahmed; Mahde Salih Hamad; Rajaa S. Najim; ThuraiaRifaat Sarhat; Kasim Sakran Abass (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective : Chronic renal failure (CRF) is one of the most prevalent diseases of human societies, especially in Iraq. Despite all advances that have been made so far, hemodialysis with all its complications is being applied as the novel treatment strategy for such individuals.Osteopontin (OPN) is a multi-functional secreted glycoprotein that plays a crucial role in and inflammatory process.Our aim was to ascertain whether circulating osteopontin,sialic acid ,and NO levels are altered in patients with CRF before and after dialysis.Design and Methods: A total of 126 patients with HD were enrolled in this study. Serum OPN levels were measured using a commercial enzymelinked immunosorbent assay kit.Results: Osteopontin and Sialic acid levels were significantly higher in haemodialysed CKD patients than predialysed CKD patients and normal healthy controls. The levels of NO was significantly lower in CRF patients pre HD when compared with healthy controls and significantly increased in post HD as compared to pre HD. Conclusion: In our study, OPN SA, NO were found to be a valuable marker of severity of CKD.